2018
DOI: 10.1080/02656736.2018.1427286
|View full text |Cite
|
Sign up to set email alerts
|

Microwave ablation induces a lower systemic stress response in patients than open surgery for treatment of benign thyroid nodules

Abstract: Microwave ablation induces a lower systemic stress response than open surgery for treatment of benign thyroid nodules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 32 publications
(36 reference statements)
1
26
0
Order By: Relevance
“…It is known that microwave ablation and surgical trauma as external environmental stimuli can both cause the body’s non-infectious stress response. The size and duration of stress response after surgery reflect the severity of surgical trauma[20,21]. Therefore, lower trauma during surgery can reduce the body’s stress response.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that microwave ablation and surgical trauma as external environmental stimuli can both cause the body’s non-infectious stress response. The size and duration of stress response after surgery reflect the severity of surgical trauma[20,21]. Therefore, lower trauma during surgery can reduce the body’s stress response.…”
Section: Discussionmentioning
confidence: 99%
“…A randomized trial in 52 patients demonstrated that MWA was followed by better general health and mental scores than thyroid surgery at 12 and 24 months [68]. In another randomized trial in 108 patients, MWA resulted in a lower visual analogue scale post-procedural pain score, and lower mean cortisol level, as a measure of stress, compared to surgery [69].…”
Section: Microwave Ablationmentioning
confidence: 99%
“…Thermal ablation is an effective outpatient procedure, with high technical feasibility [6], elevated clinical success rate [7,8], low frequency of minor (0.5-4%) [7,9] and major complications (less than 3.9%) [6], and outcomes sustained up to five years [7,[44][45][46][47]. A few comparative studies between thermal ablation and open thyroidectomy showed that the former resulted in shorter operation time, no need of hospitalization, and absence of post-treatment scar [48], less complications and side effects, no functional changes, higher patients' satisfaction [48][49][50][51][52][53] and, as a whole, lower direct and longterm costs.…”
Section: Statementsmentioning
confidence: 99%